EP1022 Primary vs interval debulking surgery for advanced epithelial ovarian cancer: survival outcomes from a tertiary greek centre. (1st November 2019) - Vlachos, D-E; Haidopoulos, D; Thomakos, N; Kalogeris, E; Rodolakis, A
Abstract : Introduction/Background: The standard treatment for advanced stage epithelial ovarian cancer consists of surgery and chemotherapy. Multiple studies have shown that complete removal of the disease is associated with better survival. However, primary debulking surgery (PDS) is not always possible, either due to the disease's extent or the patient's poor physical condition. In such cases, neoadjuvant chemotherapy (NACT) and interval debulking surgery (IDS) is preferred. The aim of the present study is to present the results from a Greek tertiary referral center as to which of the two methods has the best survival outcome. Methodology: We retrospectively analyzed all advanced stage epithelial ovarian cancer patients that were operated in our department from 1/1/2007 till 31/12/2017. We recorded the debulking type, residual disease and follow-up of the patients. Overall and progression free survival were the primary outcomes of the study. Kaplan - Meier estimator and Cox regression analysis was conducted in order to find survival rates and associated factors. Results: A total of 409 patients were recorded (214 in the PDS and 92 in the IDS group). Complete cytoreduction was achieved in 61/132 patients (46, 2%) in the IDS group and 95/277 (34, 3%) in the PDS group (p=0.019). The recurrence rate was 73.6% and 74% for the PDS and IDS groups respectively. The mean follow-up period was 6 years with a median equal of 5.1 years. The cumulative 5-year survival rate was 56% for the PDS and 40% for the IDS group, respectively. Kaplan Meier analysis revealed worse survival rates for the IDS group while no significant difference was found regarding the recurrence rates. Conclusion: Our findings support that PDS with adjuvant chemotherapy is the optimal treatment for advanced stage epithelial ovarian cancer patients. Cytoreduction rate remains the most import prognostic factor. Disclosure: Nothing to disclose.